Acute changes in lung function following controlled exposure to cookstove air pollution in the subclinical tests of volunteers exposed to smoke (STOVES) study. (23rd February 2020) - Fedak, Kristen M.; Good, Nicholas; Walker, Ethan S.; Balmes, John; Brook, Robert D.; Clark, Maggie L.; Cole-Hunter, Tom; Devlin, Robert; L'Orange, Christian; Luckasen, Gary; Mehaffy, John; Shelton, Rhiannon; et al.
Abstract: Background: Exposure to household air pollution generated as a result of cooking and heating is a leading contributor to global disease. The effects of cookstove-generated air pollution on adult lung function, however, remain uncertain. Objectives: We investigated acute responses in lung function following controlled exposures to cookstove-generated air pollution. Methods: We recruited 48 healthy adult volunteers to undergo six two-hour treatments: a filtered-air control and emissions from five different stoves with fine particulate matter (PM2.5 ) targets from 10 to 500 µg/m 3 . Spirometry was conducted prior to exposure and immediately, and three and 24 h post-exposure. Mixed-effect models were used to estimate differences in post-exposure lung function for stove treatments versus control. Results: Immediately post-exposure, lung function was lower compared to the control for the three highest PM2.5 -level stoves. The largest differences were for the fan rocket stove (target 250 µg/m 3 ; forced vital capacity (FVC): −60 mL, 95% confidence interval (95% CI) -135, 15; forced expiratory volume (FEV1 ): −51 mL, 95% CI -117, 16; mid-expiratory flow (FEF25–75 ): −116 mL/s, 95% CI -239, 8). At 3 h post-exposure, lung function was lower compared to the control for all stove treatments; effects were of similar magnitude for all stoves. At 24 h post-exposure, results were consistent with a null association for FVC and FEV1 ; FEF25–75 was lower relative to the control for the gasifier, fan rocket, and three stone fire. Conclusions: Patterns suggesting short-term decreases in lung function follow from exposure to cookstove air pollution even for stove exposures with low PM2.5 levels.